1985
DOI: 10.1017/s0021859600059451
|View full text |Cite
|
Sign up to set email alerts
|

The influence of seed type and plant density on variation in plant size of red beet (Beta vulgaris L.) crops

Abstract: In each of three experiments, five seed lots, representing multigerm, monogerm, open pollinated and hybrid types, were grown at three plant densities and the time of seedling emergence, uniformity of within-row spacing, the weight of individual shoots and roots at four occasions were recorded.Seedling emergence was more rapid in a May-sown experiment than in a March-sown experiment. The monogerm seed lot had a lower standard deviation of emergence time in the May-sown experiment and in all experiments had a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 14 publications
(13 reference statements)
1
13
0
Order By: Relevance
“…Full details of the cultural practices are described in Benjamin & Bell (1985). Briefly, red beet seed from lot C used in Expts 1, 2 and 3, was hand sown in July 1984 and subsequently thinned to give four combinations of uniformly or variably spaced seedlings of uniform or variable size.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Full details of the cultural practices are described in Benjamin & Bell (1985). Briefly, red beet seed from lot C used in Expts 1, 2 and 3, was hand sown in July 1984 and subsequently thinned to give four combinations of uniformly or variably spaced seedlings of uniform or variable size.…”
Section: Methodsmentioning
confidence: 99%
“…Expts 5, 6 and 7 have not been shape, using just a single parameter. For example, previously published, but were done a number of Bleasdale & Thompson (1963) of length to diameter has also been used to describe Full details of the cultural practices are described in shape (Bradley et al 1967;Dowker et al 1976;Benjamin & Bell (1985). In brief, these three experi-merits were sown on 22 March 1984, 8 May 1984and 26 June 1984.…”
Section: N T R O D U C T I Omentioning
confidence: 99%
“…Sowing depth, seed type, in-row plant density, and row spacing are important factors influencing yield and taproot size [12][13][14][15][16]. For example, higher in-row plant densities increase the proportion of plants with small roots but at the expense of total root yield [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…On 17 July 1985, monogerm seed clusters of cv. Monopoly (Breeders' Seeds) (see Benjamin & Bell (1985) seed lot C for details) were sown individually at a depth of 2 cm in 150 18 cm diameter pots, which had been uniformly filled with Levington compost. The pots were arranged out-of-doors where the clusters were covered with fine-grade silver sand and routine pest control and liquid feed were applied.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study by Benjamin & Bell (1985) it was pointed out that although variation in plant size is of considerable economic importance in red beet there had been no extensive systematic studies of the causes of this variation. This earlier study showed that non-hybrid beets were as uniform as F 1 hybrid beets, indicating that agronomic factors rather than genetic factors were responsible for the variation observed.…”
Section: Introductionmentioning
confidence: 99%